Prevalence, Risk Factors and Cutoff Values for Bronchial Hyperresponsiveness to Provocholine in 7-Year-Old Children - Jung, Sungsu; Suh, Dong In; Lee, So-Yeon; Yoon, Jisun; Cho, Hyun-Ju; Kim, Young-Ho; Yang, Song-I; Kwon, Ji-Won; Jang, Gwang Cheon; Sun, Yong Han; Woo, Sung-Il; Youn, You-Sook; et al. (Allergy, asthma & immunology research, 2018)
A US Food and Drug Administration (FDA)-approved drug methacholine chloride (Provocholine®) was recently introduced to Korea where it is now widely used in clinical practice. We aimed to evaluate the prevalence, risk factors and cutoff value of bronchial hyperresponsiveness (BHR) to Provocholine in 7-year-old children. Six hundred and thirty-three children from the Panel Study on Korean Children who visited 16 regional hospitals were evaluated. Skin prick tests, spirometry and bronchial provocation tests for Provocholine as well as a detailed history and physical examinations were performed. The bronchial provocation test was reliably performed on 559 of these children. The prevalence of ever-diagnosed asthma via medical records was 7.7%, and that of current asthma (wheezy episode in the last 12 months + diagnosed asthma by physicians) was 3.2%. The prevalence of BHR to Provocholine was 17.2% and 25.8%, respectively, for a PC20 < 8 and < 16 mg/mL. The risk factors for BHR (PC20 < 16 mg/mL) were atopic dermatitis diagnosis and current dog ownership, whereas those for current asthma were allergy rhinitis diagnosis, a history of bronchiolitis before the age of 3, recent use of analgesics/antipyretics and maternal history of asthma. The BHR prevalence trend showed an increase along with the increased immunoglobulin E (IgE) quartile. The cutoff value of PC20 for the diagnosis of current asthma in children at age 7 was 5.8 mg/mL (sensitivity: 47.1%, specificity: 87.4%). BHR to Provocholine (PC20 < 8 mg/mL) was observed in 17.2% of 7-year-olds children from the general population and the cutoff value of PC20 for the diagnosis of current asthma was 5.8 mg/mL in this age group. The risk factors for BHR and current asthma showed discrepancies suggesting different underlying mechanisms. Bronchial provocation testing with Provocholine will be a useful clinical tool in the future.